QTc interval in patients with multiple sclerosis: an inference from the insula of Reil?. (23rd January 2017) - Turri, G.; Calabrese, M.; Pancheri, E.; Monaco, S.; Gajofatto, A.; Marafioti, V.
Abstract : Background and purpose: The aim of this study was to investigate the correlation between the duration of the QTc interval and the brain lesion load at the level of the structures involved in superior autonomic control (insula, cingulate cortex and amygdala‐hippocampus) in multiple sclerosis (MS) patients. Methods: Thirty‐one consecutive patients with relapsing−remitting MS were recruited. The QT interval was measured manually in all 12 leads by a single blinded observer, with the longest QT value adjusted for heart rate by using the Bazett's formula. All patients performed a brain magnetic resonance imaging (MRI) scan including three‐dimensional double inversion recovery and three volumetric fast‐field echo sequences. The following MRI measures were obtained: (i) global and regional cortical thickness (CTh); (ii) white matter lesion load volume; (iii) cortical damage blindly assessed by a trained observer who assigned, on the basis of the number of cortical lesions, a score from 0 to 5 for each of the brain areas analysed. Results: In all, 16% of the patients had an increased QTc interval. The QTc interval was correlated with disease duration, cortical insular lesion volume and grey matter lesion volume in the three examined areas and inversely correlated with global and insular CTh. Conclusions: An increased QTc interval in patients with MS may have a cerebral origin possibly driven by involvement of the insular cortex. With the recent introduction in clinical practice of treatments with potential cardiac effects such as fingolimod, the recognition of a long QTc interval could be clinically crucial and should encourage appropriate electrocardiographic monitoring in order to prevent the risk of malignant ventricular pro‐arrhythmia and iatrogenic sudden death.